2004
DOI: 10.1016/j.jmwh.2003.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Building evidence for practice: a pilot study of newborn bulb suctioning at birth*1

Abstract: The purpose of the study was to examine the effects of bulb suctioning on healthy, term newborns and the feasibility of conducting a large-scale study of this practice. In a randomized, controlled two-group design pilot study, 10 newborns received oronasopharyngeal bulb suctioning at birth and 10 did not. Differences in Apgar scores, heart rates, and oxygen saturation levels were determined. Infants were randomized to groups before delivery. The participants were 20 term, healthy newborns of uncomplicated preg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…Interestingly, a median of 24 seconds was required to place nasopharyngeal tube in the present study, thus we do not recommend that method as first line intervention in infants with severe respiratory problems. Suctioning: Whereas suctioning was recommended in old guidelines and textbooks, it is nowadays considered unnecessary and potentially harmful and was deleted in internal guidelines [1,20]. Nevertheless, in our analysis about 25% of infants were suctioned and total time spend for suctioning varied but lasted up to three minutes.…”
Section: Discussionmentioning
confidence: 77%
“…Interestingly, a median of 24 seconds was required to place nasopharyngeal tube in the present study, thus we do not recommend that method as first line intervention in infants with severe respiratory problems. Suctioning: Whereas suctioning was recommended in old guidelines and textbooks, it is nowadays considered unnecessary and potentially harmful and was deleted in internal guidelines [1,20]. Nevertheless, in our analysis about 25% of infants were suctioned and total time spend for suctioning varied but lasted up to three minutes.…”
Section: Discussionmentioning
confidence: 77%
“…Avoiding unnecessary suctioning helps prevent the risk of induced bradycardia due to suctioning of the nasopharynx. 101,102 Deterioration of pulmonary compliance, oxygenation, and cerebral blood flow velocity shown to accompany tracheal suction in intubated infants in the neonatal intensive care unit also suggests the need for caution in the use of suction immediately after birth. [103][104][105] This recommendation remains unchanged.…”
Section: When Amniotic Fluid Is Clearmentioning
confidence: 99%
“…Oxygen saturations over the first 10 minutes from birth: Data were presented in different ways in different studies, precluding a comprehensive meta-analysis of all studies that reported data on this outcome. Two RCTs 9 , 27 (200 participants) and 2 observational studies 14 , 29 (418 participants) found lower oxygen saturations in those receiving suctioning within first 10 minutes, while two other RCTs 5 , 24 did not find significant differences. All evidence was of very low certainty.…”
Section: Discussionmentioning
confidence: 94%
“…The SR included 9 RCTs 3 , 4 , 5 , 9 , 24 , 25 , 26 , 27 , 28 and 2 14 , 29 observational studies enrolling a total of 1514 newborn infants (1096 in RCTs, 418 in observational studies) ( Table 1 ). All the RCTs only recruited term newborn infants except for one 26 that recruited newborn infants >35 weeks.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation